Analysis of the Impact of Black Tea Waste on The Fertility Quality of Rainbow Chili Plants (Capsicum annum L.) - Iskandar, Suhendra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Black tea is a drink commonly consumed in Indonesia, so it is not uncommon for dregs to be found to be wasteful. Waste is a serious problem that, if not handled properly, will have specific environmental impacts. Many people use tea waste as fertilizer without knowing the danger it causes to plants without further processing. This research aimed to analyze the effects of black tea waste on the fertility quality of rainbow chili plants (Capsicum annum L.). The type of research is qualitative research. The method used in this research is qualitative observation to observe the maximum height, the time to reach the maximum height, the entire leaf width, the time when the first flower appears, the time when the first fruit appears when the first fruit matures, the length of the first fruit, and the middle circumference of the first fruit of the rainbow chili plants (Capsicum annum L.) which were planted in potting soil given black tea waste with different ratio. From all the parameters observed, it was found that the best quality of rainbow chili plants (Capsicum annum L.) was in potting soil with a definite ratio of not too much but also not too little. From this fact, black tea waste can fertilize plants, but with a specific maximum level limit. Excessive amounts of tea waste can trigger alkalinity in the soil, which reduces plant fertility, and the presence of active substances such as polyphenols in it can kill decomposing bacteria, which causes new problems for the soil. Further research is still needed, especially in overcoming alkalinity and the content of active substances that can kill decomposing bacteria in the soil in black tea waste before it can be made into a commercial product like planting medium.